Incentives and Equity Under Standards-Based Reform - Julian R. Betts; Robert M. Costrell (University of Massachusetts, Department of Economics, 2000)
The paper considers theoretical and empirical evidence on the impact of standards-based school reform. Our theoretical synthesis distinguishes between sorting and incentive effects of high standards, and spells out the potential tradeoffs and complementarities between enhancing efficiency and equity in student achievement. Differentiated credentials can be helpful in ameliorating tradeoffs, provided that distinct signals are clearly understood, especially between cognitive and non-cognitive skills. The paper reviews trends in state-level school accountability systems, and examines empirical evidence on the impact of increased standards and expectations on student achievement. Finally, the paper reviews some of the practical challenges facing the standards movement.
Keywords: 330